2002
DOI: 10.1007/s100670200111
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis Associated with Recurrent Erythema Multiforme Responding to Oral Acyclovir

Abstract: Erythema multiforme is a skin condition frequently associated with herpes simplex virus and has a tendency to recur. Oral acyclovir has been successful in suppression of the disease. Here we report a patient who had recurrent erythema multiforme associated with recurrent polyarthritis that responded to oral acyclovir suppression therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…It has been suggested that recurrent herpesassociated EM may be prevented by continuous treatment with low-dose oral aciclovir (e.g. 400 mg twice daily; [160][161][162][163][164][165][166][167] or valaciclovir (168).…”
Section: Other Diseases Associated With Hsv-1 Infectionmentioning
confidence: 99%
“…It has been suggested that recurrent herpesassociated EM may be prevented by continuous treatment with low-dose oral aciclovir (e.g. 400 mg twice daily; [160][161][162][163][164][165][166][167] or valaciclovir (168).…”
Section: Other Diseases Associated With Hsv-1 Infectionmentioning
confidence: 99%
“…Famciclovir may also be useful as prophylactic anti‐HSV therapy for cutaneous laser resurfacing (Alster and Nanni, 1999) in patients with a strong history of HSV. Recurrent herpes‐associated erythema multiforme may be controlled by continuous treatment with low‐dose oral ACV (Lemak et al , 1986; Morel and Barth, 1986; Molin, 1987; Huff, 1988; Tatnall et al , 1995; Cheriyan and Patterson, 1996; Molnar and Matulis, 2002), also in children (Weston and Morelli, 1997). One RCT of continuous ACV therapy in recurrent erythema multiforme (Tatnall et al , 1995) demonstrated that 400 mg twice daily completely suppresses recurrent attacks and, in some cases, may induce disease remission.…”
Section: Prophylactic Therapy Of Recurrent Oral and Perioral Hsv‐1 Inmentioning
confidence: 99%
“…A similar case was reported wherein the recurrent cutaneous lesions of erythema multiforme and polyarthritis responded to oral acyclovir [13]. The resolution of the cutaneous lesions as well as the arthritis with anti-viral drugs could be due to the common pathogenesis of the two conditions which would require further studies.…”
Section: Discussionmentioning
confidence: 84%